Breastfeeding as Worship: “An Islamic Perspective on Stunting Prevention” a case study conducted in Southeast Sulawesi - Mar, Nur Azaliah; Kuraedah , St; Nur Sahiral Layaly (Journal of Scientific Insights, 2025)
This study aims to analyze the relevance of the Qur’anic injunction on two-year breastfeeding to stunting prevention and its contribution to public health strategies in Southeast Sulawesi through a tafsīr maudhū‘i approach and empirical survey. The research employed a mixed-methods design, combining thematic exegesis of Qur’anic verses on breastfeeding with field surveys conducted in Katobu and Palangga districts. Data were collected from 100 respondents, supplemented by interviews and focus group discussions (FGDs), and analyzed using thematic analysis and Pearson correlation in SPSS to examine the relationship between two-year breastfeeding practices and stunting prevalence. Findings reveal that Katobu, which implemented nutrition counseling grounded in Islamic values, achieved a more significant reduction in stunting rates compared to Palangga. Cross-sectoral collaboration among health workers, religious leaders, and community health cadres enhanced maternal adherence to medical recommendations and fostered awareness of breastfeeding as a religiously meritorious act. This approach proved effective in overcoming socio-cultural and economic barriers while strengthening mothers’ motivation to practice sustained breastfeeding. The study proposes an integrative educational model based on three pillars—medical counseling, spiritual education, and community mentoring—that can be replicated in other regions as a framework for stunting prevention. Moreover, these findings carry broader implications for maternal and child health and contribute to achieving the Sustainable Development Goals (SDGs), particularly SDG 2 (Zero Hunger), SDG 3 (Good Health and Well-being), SDG 4 (Quality Education), and SDG 17 (Partnerships for the Goals).